Violations of the Central American migrant women right to health from a gender and intersectionality perspective - Graíño Calaza, Irene (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2022)
In the midst of an increase in global migration, and particularly due to the persistent conflicts in Central America, Central American women have been suffering specific human rights violations. This work, from a gender and intersectional perspective, takes an approach to the violations of their human rights, and their economic, social, cultural and environmental rights, with a specific focus on the right to health. Likewise, the research aims to contribute with a series of proposals in the form of public policies for an integral development of migrations, focusing and prioritising the human rights of migrants.
Keywords: Central American migrant women; Human rights; Mexico; Migration policies; Intersectionality; Feminisms; Human rights violations; ESCE rights